PELATIHAN DAN PENYULUHAN MANFAAT CIPLUKAN BAGI KESEHATAN DAN BUDIDAYANYA DI KECAMATAN SUMBERWRINGIN DAN KECAMATAN MAESAN KABUPATEN BONDOWOSO - Tuti Kusumaningsih; Rini Devijanti Ridwan; Sidarningsih Sidarningsih (Universitas Airlangga, 2021)
AbstractCiplukan is a wild plant with the Latin name Physalis angulata L which grows a lot in rice fields and community gardens. Ciplukan plants that grow wild everywhere, at first glance it seems that there is no price, even though besides being rich in benefits, the price of ciplukan fruit is quite fantastic Rp. 100.000,-/kg. Bondowoso has 23 sub-districts, including Maesan and Sumberwringin sub-districts. Currently, there are many youth communities emerging in the two sub-districts, including the MPK 8320 and FPS communities. The activities of the two communities include hydroponic training, plant nurseries, economic development, etc. For this reason, the Community Service Team of the Faculty of Dentistry, Universitas Airlangga designed an activity to combine the existing problems in community groups, namely the lack of knowledge or information about the benefits to health, economic value, and cultivation of ciplukan plants. The existence of this problem causes community members not to have the courage to cultivate ciplukan plants, the low level of income from community members makes it difficult to find sources of funds to cultivate ciplukan plants. The purpose of this activity is to increase knowledge and skills about the health benefits and cultivation of ciplukan which will have an impact on improving the economy. The solutions offered are 1. Providing counseling and promoting ciplukan as a toga plant and its health benefits. 2. As an initial stage, distributing ciplukan plants to the community around the community 3. Providing counseling about ciplukan cultivation. This activity received a very good response from the community around the community in particular and the Bondowoso community in general, even community members have hopes and aspirations for ciplukan fruit to become the